The Experimentation of HOTS Vs ALM in the Intermediate Listening Class of EFL Learners - Farid Maftuh, Moh.; Rahayu, Titik; Maaliah, Eda (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2023)
Listening is a receptive skill which plays important role for most of English Depatment Students in Politeknik Negeri Madiun. Moreover it is a skill which must be tested in the the first semester and in the end of their study. All students in the third year must take English Proficiency test (EPT) as a prerequisite for graduation administration. Meanwhile most of students based on the previous study still have problems with listening skills, so it needs effective teaching methods to enhance students’ listening skills. This article aimed to investigate the difference in the result of teaching listening using HOTS and ALM (1), the difference between high and low creativity students after implementing HOTS and ALM (2), the influence of interaction between teaching learning methods on the results of students’ listening skills (3). The research method used was quasi experimental research. Data collecting method by using two instrument, listening test and questionnaire. Technique of analysing data used multifactor of variance (ANOVA) 2x2 and Tukey Test. Before conducting ANOVA test, pre-requisite test namely normality and homogenity test were done. Finally, the findings showed that the integrating High Order Thinking Skills into teaching listening was more effective than those who have low creativity. The second finding revealed that the students with high creativity have better listening skills than those who have low creativity. The last finding showed that there was an interaction between teaching methods and students’ creativity in teacing listening.